Cost‐effectiveness of icotinib versus whole‐brain irradiation with or without chemotherapy in EGFR‐mutant NSCLC patients with brain metastases. Issue 2 (19th January 2020) - Li, Wenqian; Bai, Rilan; Qian, Lei; Chen, Naifei; Zhao, Yuguang; Han, Fujun; Bai, Ling; Li, Jiaxuan; Yu, Yu; Cui, Jiuwei
Abstract: Purpose: Nonsmall cell lung cancer (NSCLC) patients with brain metastases (BM) have a poor prognosis. Despite the traditional methods including radiotherapy and chemotherapy, epidermal growth factor receptor‐tyrosine kinase inhibitors (EGFR‐TKIs) might benefit patients on survival and quality of life. We investigated the cost‐effectiveness of icotinib compared with whole‐brain irradiation (WBI) with or without chemotherapy for NSCLC patients with BM. Materials and methods: A Markov model was conducted based on the data of BRAIN trial. We compared the economic benefit between icotinib and the combination of WBI and WBI plus chemotherapy group. We considered disease progression as intracranial progression and overall progression separately. Sensitivity analyses were performed to observe the stability of the model. The willingness‐to‐pay (WTP) was set as 3× per capita gross domestic product ($25929/quality‐adjusted life year [QALY]) from the Chinese healthcare perspective. Results: When considering progression as intracranial progression and overall progression, respectively, the incremental cost‐effectiveness ratio was $14 882.64/QALY and $13 484.21/QALY between icotinib and WBI/WBI‐chemotherapy. Besides, both of the average cost‐effective ratio (ACER) and net benefit showed advantage of icotinib (ACER: $34 521.42/QALY for intracranial progression and $36 562.63/QALY for overall progression; net benefit: –$8407.36 for intracranial progression and –$9836.41 for overall progression). One‐way sensitivity analyses demonstrated that no thresholds were encountered. The probabilistic sensitivity analyses showed even at a WTP under $18 000/QALY, icotinib could be cost‐effective. Conclusion: : Icotinib was cost‐effective compared with WBI with or without chemotherapy.